Implementation of Good Governance and Government Internal Control System In Regional Financial Management: A Case Study of Semarang City Government - Rimi Gusliana Mais; Jayanti Icha Lufhianti; Syifa Dara Fauziah; Istiqomah Triani Putri (Labkat Press KA FTIK UNIKOM, 2025)
This study examines the implementation of good governance principles and the Government Internal Control System (SPIP) in the regional financial management of Semarang City Government. Motivated by audit findings from the Audit Board of Indonesia (BPK) that identified irregularities in budget utilization and asset management, this qualitative research employs a content analysis approach to examine official documents, including the Government Agency Performance Report (LKjIP), Local Government Financial Statements (LKPD), and BPK audit reports for the 2023 fiscal year. The analysis focuses on three dimensions of good governance, accountability, transparency, and public participation as well as the maturity level of SPIP implementation. The findings reveal that Semarang City Government achieved an AKIP score of 88.5 with a “Satisfactory” predicate, received Unqualified Opinions (WTP) for eight consecutive years, and obtained an SPIP maturity score of 3.086 at the “Defined” level. Transparency is facilitated through an official digital portal and recognition through the 2023 Digital Government Award, while public participation is promoted through the “Sapa Mbak Ita” digital platform. These findings indicate the city government's commitment to building transparent, accountable, and community-responsive financial governance. This study provides empirical evidence on the integration of internal control systems and good governance principles at the local government level, offering practical recommendations to strengthen accounting and internal control systems in public sector organizations.